Pelatihan Finishing Kayu Jati Belanda Bernilai Tinggi Bagi Kelompok Masyarakat Gunung Kelua - Syafi’i; Abdul Rasyid Zarta; Zahrotul Isti’anah Marroh; Muhammad Tahrir; Teguh Rizali Zahroni; Taman Alex; Yusdiansyah; Eva Nurmarini; Heriad Daud; Ita Merni Patulak (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The High-Value Dutch Teak Wood Finishing Training for Gunung Kelua Community Group is a programme that aims to improve the skills and knowledge of the local community in the finishing process of Dutch teak wood, a type of wood with high economic value in the international market. The programme is designed to support the development of small and medium industries (SMIs) in the region, focusing on sustainable and responsible use of local natural resources. Through this training, participants are expected to learn modern finishing techniques that can improve the aesthetics and functionality of the final product, understand the principles of effective design and project management as well as an understanding of environmentally friendly and anti-pollutant products. The training also covers important aspects such as knowledge of wood species and characteristics, selection of eco-friendly materials, surface treatment, finish application, and post-finish care, all of which are key components in the production of high-value Dutch teak. By adopting both practical and theoretical learning methods, the programme provides participants with hands-on skills and equips them with a deep understanding of the need to use environmentally friendly paint-based materials. The ultimate goal is to help the Gunung Kelua community group expand their market, increase income, contribute to the sustainable development of the local economy as well as sensitise them to the use of environmentally friendly materials. This programme is expected to become a training model that can be adapted and applied in other regions in Indonesia, especially in areas that have potential natural wood resources but still need technical support and capacity in processing and marketing high-quality products. Keywords: Training; Wood Finishing; Dutch Teak